Functional brain connectivity at rest changes after working memory training - Jolles, Dietsje D. (Hum Brain Mapp, 2011)
Networks of functional connectivity are highly consistent across participants, suggesting that functional connectivity is for a large part predetermined. However, several studies have shown that functional connectivity may change depending on instructions or previous experience. In the present study, we investigated whether 6 weeks of practice with a working memory task changes functional connectivity during a resting period preceding the task. We focused on two task‐relevant networks, the frontoparietal network and the default network, using seed regions in the right middle frontal gyrus (MFG) and the medial prefrontal cortex (PFC), respectively. After practice, young adults showed increased functional connectivity between the right MFG and other regions of the frontoparietal network, including bilateral superior frontal gyrus, paracingulate gyrus, and anterior cingulate cortex. In addition, they showed reduced functional connectivity between the medial PFC and right posterior middle temporal gyrus. Moreover, a regression with performance changes revealed a positive relation between performance increases and changes of frontoparietal connectivity, and a negative relation between performance increases and changes of default network connectivity. Next, to study whether experience‐dependent effects would be different during development, we also examined practice effects in a pilot sample of 12‐year‐old children. No practice effects were found in this group, suggesting that practice‐related changes of functional connectivity are age‐dependent. Nevertheless, future studies with larger samples are necessary to confirm this hypothesis. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.